European Competence Network on Mastocytosis (ECNM): 20-Year Jubilee, Updates, and Future Perspectives - Valent, Peter; Hartmann, Karin; Bonadonna, Patrizia; Sperr, Wolfgang R; Niedoszytko, Marek; Hermine, Olivier; Kluin-Nelemans, Hanneke C; Sotlar, Karl; Hoermann, Gregor; Nedoszytko, Boguslaw; Broesby-Olsen, Sigurd; Zanotti, Roberta; et al. (The journal of allergy and clinical immunology. In practice, 2023)
In 2002, the European Competence Network on Mastocytosis (ECNM) was launched as a multidisciplinary collaborative initiative to increase the awareness and to improve diagnosis and management of patients with mast cell (MC) disorders. The ECNM consists of a net of specialized centers, expert physicians, and scientists who dedicate their work to MC diseases. One essential aim of the ECNM is to timely distribute all available information about the disease to patients, doctors, and scientists. In the past 20 years, the ECNM has expanded substantially and contributed successfully to the development of new diagnostic concepts, and to the classification, prognostication, and treatments of patients with mastocytosis and MC activation disorders. The ECNM also organized annual meetings and several working conferences, thereby supporting the development of the World Health Organization classification between 2002 and 2022. In addition, the ECNM established a robust and rapidly expanding patient registry and supported the development of new prognostic scoring systems and new treatment approaches. In all projects, ECNM representatives collaborated closely with their U.S. colleagues, various patient organizations, and other scientific networks. Finally, ECNM members have started several collaborations with industrial partners, leading to the preclinical development and clinical testing of KIT-targeting drugs in systemic mastocytosis, and some of these drugs received licensing approval in recent years. All these networking activities and collaborations have strengthened the ECNM and supported our efforts to increase awareness of MC disorders and to improve diagnosis, prognostication, and therapy in patients.
Keywords: Forecasting; předpověď; mastocyty; Mastocytosis; systémová mastocytóza; mastocytóza; lidé; Mast Cells; Mastocytosis, Systemic; Humans